PERLINDUNGAN HUKUM NASABAH TERHADAP BOCORNYA RAHASIA DATA M-BANGKING DI ERA DIGITAL - Khansa Inggita Sari; Maria Claudita Abigael; Ambar Krisna Putri (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
The advancement of digital technology has brought about significant transformation in the banking sector, especially through mobile banking (m-banking) services that offer convenience and efficiency of financial transactions. However, these services also present the risk of customer data leakage that can threaten trust in the digital banking system. This study aims to examine legal protection for customers against data leakage in m-banking services in Indonesia, evaluate the responsibility of service providers, and provide effective legal solutions to address these challenges. Using normative legal methods and descriptive analysis, this study highlights the role of laws such as the Banking Law, the ITE Law, the PDP Law, and regulations from the OJK and Bank Indonesia. This study finds that despite the existence of an adequate legal framework, implementation in the field is still weak due to lack of supervision, low user awareness, and increasing threats of cybercrime. This study recommends strengthening regulations, customer education, and the implementation of layered security technology to ensure optimal customer data protection.